GAMBARAN PEKERJAAN IBU HAMIL TRIMESTER I DENGAN KEJADIAN ABORTUS DI RSIA KIRANA SIDOARJO: OCCUPATION OF PREGNANT WOMEN IN TRIMESTER I WITH THE EVENT OF ABORTUS IN RSIA KIRANA SIDOARJO - Jelita, Reynaldis; Juaria, Henny (Universitas Muhammadiyah Sidoarjo, 2015)
Working outside for the first trimester pregnant women is actually a high risk that causing an abortion or miscarriage. In a first trimester of pregnancy, the reproductive organs have not been able to hold the conception because placenta unformed completely yet. If the first trimester pregnant women become too tired and less of rest, it can be happened a miscarriages. Miscarriage is a threats or the unintentional expulsion of the conception before it is viable. It is so unfortunate, if a wanted pregnancy has to end with miscarriage. Based on the survey, most of the first trimester pregnant women in RSIA KiranaSidoarjo on 2013 is a career women 89,44%. This research is undertaken to know the effects of working to the first trimester pregnant women with the incident ofmiscarriage in the RSIA Kiranasidoarjo on 2013. This study was descriptive research and used total sampling. The population was taken from 161 people of all the first trimester pregnant women who undergo a miscarriage. The research showed that career women more experience a miscarriage (79,17%) than no career women (64,7%). A working first trimester pregnant women is highly risked a miscarriage.